Penjualan on-line berbasis media sosial dalam perspektif ekonomi Islam - M. Nur Riyanto Al-Arif (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Contemporary transactions along with the development of existing technologies have given rise to other forms of trading i.e. on-line trading. This paper aims to look at how the Islamic economic perspectives associated with on-line trading. The method used in this paper was library research. On-line trading had fulfilled the shariah principle, i.e. al-aqid, s}ighah, al-ma’qud alaih and the goal of the transaction. The transaction models that can be adopt in trading on line are bay’ al-murabah}ah and bay’ al-salam. Trading online had several advantage for buyer and seller, but trading on-line also had several problems. So, we must to had a strategy to minimize the various problems that may arise.